Conservation agriculture has no significant impact on sheep digestive parasitism - Mansour El Hamdi, Sihem; Sassi, Limam; Rekik, Mourad; Dhehibi, Mokhtar; M'hamed, Hatem Cheikh; Gharbi, Mohamed (Frontiers Media, 2023)
Conservation agriculture (CONS A) is a sustainable agriculture system based on crop rotation with no tillage. It has various environmental advantages compared to conventional agriculture (CONV A): decreased water evaporation, erosion, and CO2 emissions. In this first study of its kind, we aim to evaluate the impact of this type of agriculture on sheep gastrointestinal parasites. Two lamb groups aged between 5 and 10 months were randomly included to graze separately on CONS A and CONV A pastures. Each group was composed of two batches of three lambs, and these were followed up for two rearing months. Liveweight, hematological parameter variation, and digestive parasites were studied. At the end of the study period, lambs were slaughtered the carcass yield was determined, and a helminthological autopsy was performed on the digestive tracts of the animals to estimate different parasitological indicators. There was no difference between lambs reared on CONS A and those reared on CONV A for all parasite indicators (infestation intensity, abundance, and prevalence). The same trend was also obtained for hematological parameters, liveweight evolution, and carcass yield. These results prove that there is no impact of CONS A on the sheep’s digestive parasitism. Further studies are needed to support these findings on larger animal samples and to investigate the impact of conservation agriculture on other parasite species. Similar studies could also be conducted on ruminant species.